Al-Ijarah Al-Maushufah fi Al-Dzimmah in the Study of Islamic Financial Economics - Syaichoni, Ahmad (Economica: Jurnal Ekonomi Islam, 2020)
Abstract: In the modern era like today, business transactions have developed along with technological developments. One form of development of business transactions is the modification of classic-contemporary contracts. One form of modification of the contract is the al-Ijarah al-Maushufah fi al-Dzimmah contract. This contract is developed for financing activities of Islamic financial institutions, especially the banking sector, and as an alternative to the financing scheme for infrastructure projects. This research aims to study the issue of al-Ijarah al-Maushufah fi al-Dzimmah in Islamic financial economics. This research is library research with a normative approach. The data analysis used is content analysis and critic analysis. According to the findings of this study, al-Ijarah al-Maushufah fi al-Dzimmah is a contract development employed to suit the community's demands. The monotheism framework underpins the creation of al-Ijarah al-Maushufah fi al-Dzimmah in the study of Islamic financial economics. Tauhid is founded on evolutionary equilibrium and consciousness as a manifestation of monotheism in developing this product. The evolution and consciousness of Islamic banking products into new scientific jewels inside the treasures of Islamic financial economics is the theoretical implication of this research. Compared to previous research, the originality of this study is that the al-Ijarah al-Maushufah fi al-Dzimmah contract is reviewed in terms of Islamic financial economics with a tauhid framework.Abstrak: Era modern seperti saat ini, transaksi bisnis mengalami pengembangan seiring dengan berkembangnya teknologi. Salah satu bentuk pengembangan transaksi bisnis adalah modifikasi akad klasik-kontemporer. Salah satu modifikasi akad tersebut adalah akad al-Ijarah al-Maushufah fi al-Dzimmah. Akad ini merupakan akad yang dikembangkan dalam kegiatan pembiayaan pada lembaga keuangan syariah, khususnya pada bidang perbankan dan merupakan produk alternatif skema pembiayaan yang digunakan untuk pembangunan proyek infrastruktur. Tujuan penelitian ini untuk menganalisis konsep al-Ijarah al-Maushufah fi al-Dzimmah dalam kajian ekonomi keuangan Islam. Penelitian ini menggunakan library research dengan pendekatan normatif. Analisis data yang digunakan adalah analisis isi dan analisis kritis. Hasil penelitian ini menunjukkan bahwa al-Ijarah al-Maushufah fi al-Dzimmah merupakan pengembangan akad yang digunakan untuk memenuhi kebutuhan masyarakat. Pengembangan al-Ijarah al-Maushufah fi al-Dzimmah dalam kajian ekonomi keuangan Islam berdasarkan kerangka tauhid. Konsep tauhid dalam pengembangn produk ini didasarkan pada ekuilibrium evolusioner dan kesadaran sebagai manifestasi tauhid. Implikasi penelitian ini dari segi teoretis adalah pengembangan dan inovasi produk perbankan syariah menjadi khazanah keilmuan baru dengan dalam khazanah ekonomi keuangan Islam. Orisinalitas penelitian ini dibandingkan dengan penelitian sebelumnya adalah akad al-Ijarah al-Maushufah fi al-Dzimmah ditinjau dalam pandangan ekonomi keuangan Islam dengan kerangka tauhid.